PENGECORAN ALUMINIUM MATRIKS KOMPOSIT BERPENGUAT CARBON NANOTUBE (CNT) DENGAN VARIASI PENAMBAHAN SERBUK MAGNESIUM - Syahid, Muhammad; Elyeser, Elyeser; Hayat, Azwar (Jurnal Rekayasa Mesin, 2023)
Aluminum matrix composite reinforced CNT have been developed to improve the mechanical properties of aluminum. In this study, the melting of Aluminum 1100 reinforced Carbon Nanotube (1 wt.% CNT) with variations in the addition of Magnesium powder was carried out by the slurry-based method. The casting of the specimens is carried out using a metal mold. CNT powder was first mixed with magnesium powder at 60°C. Then the aluminum is melted to a temperature of 700°C until it melts, then the temperature is lowered to 500°C or the texture has changed to be like mush (slurry based) and then mixed with CNT powder and Magnesium powder are added. After that the alloy was raised again at 720°C for 30 minutes and the stirring process was carried out, after that it was poured into a metal mold with a mold temperature of around 400°C. The samples were then analyzed for mechanical properties and microstructure observations.  The results of the Vickers hardness test before the addition of Mg powder and CNT were 36.7 HV. While after the variation of adding 1wt.% Mg powder, the hardness of the specimen increased to 44.5 HV, the variation of adding 3% Mg powder was 45.3 HV, and the variation of adding 5% Mg powder reached a hardness value of 46 HV. The tensile test results on 3% Mg powder is 241.6 MPa. The wear test results show the wear rate value for the 1% Mg variation of 0.146 mg/s, the 3% Mg variation of 0.106 mg/s, and the 5% Mg variation with a wear rate value of 0.093 mg/s. The α-Al phase is the dominant phase formed, where the grain size and grain boundaries in the 3% Mg variation have a relatively small size and the spread of CNT is evenly distributed in the alloy, so the addition of Mg to the alloy can help spread CNT in Aluminum alloys.